2015
DOI: 10.1007/s11356-014-3965-6
|View full text |Cite
|
Sign up to set email alerts
|

Fructans, ascorbate peroxidase, and hydrogen peroxide in ryegrass exposed to ozone under contrasting meteorological conditions

Abstract: Ozone (O3) is the most abundant tropospheric oxidant as well as an important component of photochemical pollution. Once inside the plant, ozone can produce reactive oxygen species that change the antioxidative pool and the carbohydrate metabolism. The current study aimed to analyze whether the contents and the composition of the fructan, the ascorbate peroxidase activity, and the H2O2 accumulation were changed in Lolium multiflorum ssp. italicum cv. Lema plants as response to short-term exposure to ozone and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…As reported throughout this review, carbohydrate accumulation is consistently implicated in increased tolerance to abiotic stresses (Rosa et al, 2009). A similar effect following ozone exposure might explain how in Italian ryegrass higher ozone concentrations substantially increased leaf fructose content and altered fructan polymerization (Moretto, Sandrin, Itaya, Domingos, & Figueiredo-Ribeiro, 2009;Pasqualetti et al 2015). Indeed, substantial increases in leaf sucrose and starch content were reported in wheat (Meyer et al, 1997) following exposure to high ozone levels.…”
Section: On Cool -Season Grass Metabolismmentioning
confidence: 69%
See 2 more Smart Citations
“…As reported throughout this review, carbohydrate accumulation is consistently implicated in increased tolerance to abiotic stresses (Rosa et al, 2009). A similar effect following ozone exposure might explain how in Italian ryegrass higher ozone concentrations substantially increased leaf fructose content and altered fructan polymerization (Moretto, Sandrin, Itaya, Domingos, & Figueiredo-Ribeiro, 2009;Pasqualetti et al 2015). Indeed, substantial increases in leaf sucrose and starch content were reported in wheat (Meyer et al, 1997) following exposure to high ozone levels.…”
Section: On Cool -Season Grass Metabolismmentioning
confidence: 69%
“…However, Plazek et al (2001) reported that exposure of meadow fescue plants to high ozone concentrations did not alter membrane permeability. In contrast, Pasqualetti et al (2015) using Italian ryegrass (Lolium multiflorum) reported a marked increase in hydrogen peroxide levels after exposure to increased ozone concentrations.…”
Section: Floodmentioning
confidence: 80%
See 1 more Smart Citation
“…As one of the most toxic air pollutants, elevated O 3 concentrations could exert serious consequences on plant growth, physiological metabolisms and morphological characteristics [8][9][10][11][12]. The adverse effects of elevated O 3 concentrations on plants including herb species have been well known [13,14]. Elevated O 3 concentration led to leaf injury, decreased photosynthetic rate, and inhibited growth and accelerated senescence of many plant species [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Actually, plants including herb species have developed antioxidative systems to protect plant cells by regulating the production rate or content of intra-cellular ROS such as hydrogen peroxide (H 2 O 2 ) and superoxide anion (O 2 • − ). Changes in the activities of defense enzymes in leaves such as superoxide dismutase (SOD, catalase (CAT), peroxidase (POD) and ascorbate peroxidase (APX) could play an important role in preventing and alleviating the adverse impacts of elevated O 3 by scavenging ROS in many plants [9,14,17,20].…”
Section: Introductionmentioning
confidence: 99%